Ethikmanagement im Krankenhaus Unternehmens- und Wertekultur als Erfolgsfaktor für das Krankenhaus - Wehkamp, Kai (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2017)
Good hospital executives help to ensure that medical and nursing care for patients is of a high standard and at the same time secure the economic livelihood of their home. Both within the company and in the interaction with the public and politics, it is important to constantly mediate between the demands for economy and good medicine. Managers gain persuasiveness through a precise reference to the values and goals of medicine and economy. A constructive understanding of ethics - not only at the level of patient care, but also at the level of the organization - is an essential competence for hospital management.